The Effect of Good Corporate Governance on Employee Performance Through Job Satisfaction - Rini Lestari; Kania Nurcholisah; Nurfahmiyati; Ririn Sri Kuntorini (MIMBAR : Jurnal Sosial dan Pembangunan, 2024)
This article aims to empirically examine the effect of Good Corporate Governance (GCG) principles on job satisfaction and employee performance, and analyze the role of job satisfaction in mediating the effect of GCG on employee performance.The research method used is a verifiable research method with a quantitative approach. The data collection technique used is a questionnaire distributed to employees who work at Islamic banking institutions in the city of Bandung. The data analysis technique used was assisted by the SEM PLS statistical technique with a sample of 118 employees of Islamic banking institutions in the city of Bandung. The results of the study show that the implementation of GCG principles has a positive and significant effect on job satisfaction and employee performance, job satisfaction has a positive and significant effect on employee performance and the implementation of GCG principles has a positive and significant effect on employee performance through job satisfaction.